Получение пленок диоксида олова для энергосберегающих газовых датчиков - Хрипунов, Геннадий Семенович; Кривошеев, Сергей Юрьевич; Новиков, Виталий Александрович; Пирогов, Александр Викторович (НТУ "ХПИ", 2014)
Проведена оптимизация технологического процесса получения газочувствительных пленок диоксида олова методом магнетронного распыления с последующим отжигом на воздухе. Экспериментально доказано, что газочуствительность пленок диоксида олова увеличивается при увеличении концентрации кислорода в составе распыляющего газа, снижении температуры подложки и уменьшение толщины слоя. Рассмотрены физические механизмы, обуславливающие наблюдаемые экспериментальные закономерности.

The influence of the technological process preparation of the gas sensing properties to reducing gases tin dioxide films it was studied. Technological process consists preparation of the tin oxide films by magnetron DC sputtering and subsequent annealing films in air at the temperature of 500 ⁰C during 10 hours. It has been established that the increase of oxygen concentration in the gas composition in during magnetron sputtering process and increase the substrate temperature results to monotonic decrease of the tin dioxide films gas sensing properties. This is due to decreasing in the initial electrical conductivity and increasing the degree of the electrical conductivity dependence on the gaseous impurities concentration. For given values of the oxygen concentration in the composition sputtering gas and given values substrate temperature the reducing of the tin dioxide films thickness below the critical thickness of crystallization to results a significant increase gas sensing properties. This is due to the fact that the subsequent annealing of amorphous films provides a fine-grained structures. Apparently the size of coherent scattering regions correspond to the size of the annealed films formed during the growth of these films tiny amorphous particles. As a result, the developed grain boundary surface of the annealed films of tin dioxide dramatically increases the likelihood of sorption of gaseous impurities analyzed.
Preparation of the tin dioxide films for energy-saving gas sensor
Keywords: газочувствительность; распыление магнетронное; отжиг; gas sensing properties; films; tin dioxide; magnetron sputtering; annealing